A Semimechanistic Pharmacokinetic Model for Depot Medroxyprogesterone Acetate and Drug–Drug Interactions With Antiretroviral and Antituberculosis Treatment. Issue 4 (1st July 2021) - Francis, Jose; Mngqibisa, Rosie; McIlleron, Helen; Kendall, Michelle A; Wu, Xingye; Dooley, Kelly E.; Firnhaber, Cynthia; Godfrey, Catherine; Cohn, Susan E.; Denti, Paolo; ,
Abstract : Depot medroxyprogesterone acetate is an injectable hormonal contraceptive, widely used by women of childbearing potential living with HIV and/or tuberculosis. As medroxyprogesterone acetate is a cytochrome P450 (CYP3A4) substrate, drug–drug interactions (DDIs) with antiretroviral or antituberculosis treatment may lead to subtherapeutic medroxyprogesterone acetate concentrations (< 0.1 ng/mL), resulting in contraception failure, when depot medroxyprogesterone is dosed at 12‐week intervals. A pooled population pharmacokinetic analysis with 744 plasma medroxyprogesterone acetate concentrations from 138 women treated with depot medroxyprogesterone and antiretroviral/antituberculosis treatment across three clinical trials was performed. Monte Carlo simulations were performed to predict the percentage of participants with subtherapeutic medroxyprogesterone acetate concentrations and to derive alternative dosing strategies. Medroxyprogesterone acetate clearance increased by 24.7% with efavirenz coadministration. Efavirenz plus antituberculosis treatment (rifampicin + isoniazid) increased clearance by 52.4%. Conversely, lopinavir/ritonavir and nelfinavir decreased clearance (28.7% and 15.8%, respectively), but lopinavir/ritonavir also accelerated medroxyprogesterone acetate's appearance into the systemic circulation, thus shortening the terminal half‐life. A higher risk of subtherapeutic medroxyprogesterone acetate concentrations at Week 12 was predicted on a typical 60‐kg woman on efavirenz (4.99%) and efavirenz with antituberculosis treatment (6.08%) when compared with medroxyprogesterone acetate alone (2.91%). This risk increased in women with higher body weight. Simulations show that re‐dosing every 8 to 10 weeks circumvents the risk of subtherapeutic medroxyprogesterone acetate exposure associated with these DDIs. Dosing depot medroxyprogesterone every 8 to 10 weeks should eliminate the risk of subtherapeutic medroxyprogesterone acetate exposure caused by coadministered efavirenz and/or antituberculosis treatment, thus reducing the risk of contraceptive failure.